Development of Web-mediated Audio-Visual Listening Book to Boost the Understanding of Implicatures in the TOEFL Short Dialogues - Arifuddin Arifuddin; I Made Sujana; Nawawi Nawawi (Journal Evaluation in Education (JEE), 2023)
Purpose of the Study: Understanding implicatures in TOEFL Short Dialogues is difficult. It is essential to develop web-based media to boost implicature understanding. This current study aimed at testing the implicature inference-making ability of English teachers, identifying the factors that affect listening difficulties and developing web-mediated audio-visual books for the TOEFL. Methodology: This is a three-phase R & D model: 1) ‘Research Phase’ (Testing the English teachers listening ability; Examining factors affecting implicatures understanding; and Profiling the English teachers listening abilities); 2) ‘Development Phase’ (Constructing the test instrument; Formulating Learning Objectives; Selecting Audio-visual materials, Designing the web-mediated audio-visual book; Validating and revising the book) and ‘Production Phase’ (Dissemination and Mass Production). Main Finding: The products of the ‘Research phase’: 1) Listening ability, 2) Factors affecting listening, 3) Profile of the English teachers’ pragmatic ability. There are five primary causes of difficulty, ‘Speech Rate Delivery,’ ‘Voice,’ ‘Sentence Complexity,’ ‘Mishearing,’ and ‘Colloquial.’ The product of the ‘Development Phase’ is a ‘Web-based audiovisual book for the TOEFL Short Dialogues.’ All lessons are aided with online links to audio and videos. Finally, the product of ‘Production Phase’ is a massed published book. Novelty/Originality of the Study: No single study has ever been reported that focused on developing a web-mediated audio-visual listening book to boost the understanding of implicatures in the TOEFL Short Dialogues.